2012
DOI: 10.1126/scitranslmed.3003155
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adenovirus-Based Vaccines Induce Broad and Sustained T Cell Responses to HCV in Man

Abstract: Currently no vaccine exists for hepatitis C virus (HCV), a major pathogen thought to infect 170 million people globally. Many studies suggest that host T cell responses are critical for spontaneous resolution of disease, and preclinical studies have indicated a requirement for T cells in protection against challenge. We aimed to elicit HCV-specific T cells with the potential for protection using a recombinant adenoviral vector strategy in a Phase I study of healthy human volunteers. Two adenoviral vectors expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
383
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(400 citation statements)
references
References 30 publications
7
383
0
3
Order By: Relevance
“…Clinical experiences with Ad vectors have shown them to be well tolerated at doses needed to induce transgene product-specific immune responses. 7,9,24 We developed AdC vectors to circumvent preexisting neutralizing antibodies, which are commonly found in humans to human Ad serotypes. 38,39 Ad-neutralizing antibodies reduce uptake of the corresponding Ad vectors and hence their ability to induce transgene product-specific immune responses.…”
mentioning
confidence: 99%
“…Clinical experiences with Ad vectors have shown them to be well tolerated at doses needed to induce transgene product-specific immune responses. 7,9,24 We developed AdC vectors to circumvent preexisting neutralizing antibodies, which are commonly found in humans to human Ad serotypes. 38,39 Ad-neutralizing antibodies reduce uptake of the corresponding Ad vectors and hence their ability to induce transgene product-specific immune responses.…”
mentioning
confidence: 99%
“…These trials demonstrated that the vaccines induced robust and functional CD4 + and CD8 + T-cell responses to multiple antigenic sites, and that these responses were sustained for up to one year. 21,23 Phase-II studies are currently underway in the USA.…”
Section: Development Of Vaccinesmentioning
confidence: 99%
“…The incidences and severity of local and systemic adverse reactions were similar to those observed in previous studies of other adenovirus vectored vaccines. 23,36 Beside, another phaseI, dose-escalation, open-label study was conducted to assess the safety and immunogenicity of a single dose of the ChAd3-EBO-Z at 3 different dosages 1 £ 10 10 , 2.5 £ 10 10 and 5 £ 10 10 vp, with 20 participants per group, respectively 33 (ClinicalTrials.gov NCT02240875) ( Table 1). The highest dosage of the experimental vaccines in this trial only a quarter of that in the previous trial.…”
Section: Non-replicative Vector-based Ebola Vaccinesmentioning
confidence: 99%